PENDIDIKAN DALAM KELUARGA - Mizal, Basidin (SCAD Independent, 2014)
The nature of a family is not only as a gathering place for the husband, wife and children. More than that, family has significant function and role in determining the fate of a nation. Allah affirms that large losses on the judgment day are when we lose our beloved family. Allah said in Surah Asy Syuura verse 45 which meant: And you will see them brought to hell in a state of submission as (felt) worthless, they saw with sluggish view. And those who believe say: ?Indeed, those losers are those who lose themselves and (lose) their family on the judgment day. Remember, actually the unjust people are in eternal doom. Family improvement in all respects should be a top priority before we prioritize other. The quality of true family is not just obtaining good test scores or material, but how parents can transfer value, character and good trait to their children, so that they could live in a better society, and can dedicate themselves to The Creator. The reciprocation of a society and the state depends heavily on good or not the education in family. Preparing qualified family members synonymous with preparing for a successful future. And responsibilities of the establishment of quality are on the shoulders of the parents.